The expansion and contraction of the apprenticeship system in Australia, 1985-2020 - Smith, Erica [Verfasser] (My University, 2021)
"This paper chronicles and analyses the expansion and contraction of the Australian apprenticeship system from 1985 to 2020. The system expanded from a small number of occupations, mainly in craft and manufacturing areas, to include many other occupations, notably in the different types of service sectors. The expansion was achieved primarily through a new type of apprenticeship, known as a traineeship, to augment the existing more traditional apprenticeships. Since 2012, the system has contracted considerably, and the participation rate of women has been affected disproportionately. The period of expansion of the system was book-ended by two major government-instigated documents, in 1985 and 2011. In 1985 a Parliamentary Committee of Inquiry into Labour Market Programs proposed the introduction of traineeships, and in 2011 an Expert Panel on Apprenticeships sought to reduce numbers through the application of specific criteria for government support, which primarily affected the occupations served by traineeships. Two sources of evidence are used to examine the expansion and contraction of the apprenticeship system: data from the national apprenticeship statistics collection maintained by the National Centre for Vocational Education Research (NCVER) and key government reports over the 35 years. A brief overview of COVID-19-related developments in 2020 is included." (Author's abstract ; BIBB-Doku)
Keywords: I 2.3.5 Australien, Ozeanien; S System beruflicher Bildung; S 1.3 Berufliche Erstausbildung; S 1.6.1 Praktika; G 1.3 Aus- und Weiterbildungsmarkt; 370; Australien; Berufsbildungssystem; Berufsausbildung; Praktikum; Berufsbildungsstatistik; Berufsbildungspolitik; 1985-2000